Effects of Fermented Cassava on Physical, Chemical, and Sensory Properties of Sokaraja Baked Getuk - Shinta Rizqoh Iktavia; Muhammad Ansori (Jurnal Pendidikan Tata Boga dan Teknologi, 2026)
This study aims to analyze the effect of the use of fermented cassava on the level of preference, physical parameters and nutritional content of Sokaraja grilled getuk. This study applied a complete random design or RAL one element with four levels of treatment, namely P0 (0% fermented cassava: 100% non-fermented cassava), P1 (80%: 20%), P2 (90%: 10%) and P3 (100%: 0%). Preference test was carried out by 40 untrained panelists using hedonic methods on color, aroma, taste, texture and overall attributes. Physical tests of color parameters were measured using the Croma Meter tool and texture using the texture analyzer tool. Chemical analysis such as the moisture content of the oven method and the protein content of the titrimetry method. Hedonic data were analyzed using the kruskal wallis test which was continued through the mann whitney test. Study findings showed that the use of fermented cassava produced a relatively equal level of preference for color, aroma, taste and overall parameters between treatments (p > 0.05) but had a real influence on texture or p less than 0.05. The use of fermented cassava tends to reduce the level of hardness so that it forms a consistency that is more tender and more in demand by panelists. In addition, the moisture content and protein content increase as the proportion of fermented cassava increases. Results of study show that fermented cassava has the potential to be used as an alternative ingredient in the development of Sokaraja grilled getuk without reducing sensory acceptance of the product.